Papa, PhD : essays on fatherhood by men in the academy - Marotte, Mary Ruth; Reynolds, Paige; Savarese, Ralph James (UPCC book collections on Project MUSE., 2011)
A collection of personal essays from men who wrestle with what it means to be a father in academia today. Organized in three sections, the stories of the contributors depict not merely a balancing act of parenting, teaching, and writing, but also the revelatory collision and occasional fusion of competing identities. Essays in the first section, "Fathers in Theory, Fathers in Praxis," focus on challenges related to merging work and parenting. The authors contemplate to what degree we engage our children in the academy, while also allowing them to grow independently, recognizing the challenge of keeping the roles of parent and teacher distinct. The second section, "Family Made," explores fatherhood against the grain and includes narratives of single dads, fathers raising children with disabilities, biracial families, and other "non-traditional" parenting situations. "Forging New Fatherhoods," the third section, articulates the strategies created by men to "balance diapers and a doctorate" or to reconcile fatherhood with professional ambition. The contributors' reflections reveal how fatherhood is instrumental to their successes and failures in the workplace, and demonstrate that the relationship between fatherhood and academia is a rich and legitimate subject for study.